Timing in Klezmer Performance - Yonatan Malin (Analytical Approaches to World Music)
This study explores aspects of timing in the performance of Jewish instrumental music from Eastern Europe, known as klezmer. Performance style is an essential aspect of the tradition; musicians today study historical recordings and teach the style in lessons and workshops. The paper thus dovetails with concerns of contemporary musicians who look back to historical sources as they continue to innovate. Three common timing features are documented: (1) variable timing within and between performances, (2) non-isochronous (unequal) beats in a genre known as the zhok or hora, and (3) a distinctive move-ahead-and-wait or accelerate-and-delay gesture that is a signature of the style more broadly and an inverse of a common timing profile in jazz (see Ashley 2002). I analyze historical recordings of a tune known as “Gasn Nign” by Jacob Hoffman with Kandel’s Orchestra (1923), Abe and Sylvia Schwartz (1920), and the Naftule Brandwein (1923). I then analyze a more recent recording of “Gasn Nign” by Alicia Svigals with Steven Greenman (1996) and a piece called “I Flow with Water Under the Ice” composed and performed by Cookie Segelstein with Joshua Horowitz (2019). Methodologies include close listening, transcription, score annotation, timing measurements using Sonic Visualiser, and customized forms of data visualization. Pedagogical materials, discussions with leading musicians, and information from workshops and lessons show how contemporary musicians understand and teach the timing features documented here. This study contributes to a growing field of timing studies in world music traditions, including the Southeastern European traditions that are closely aligned with klezmer. It contributes to the literature on aksak meters by documenting a long-short metric cycle with beats in a 3:2 ratio and by investigating the timing of rhythms that work with this cycle. It builds on London’s many meters hypothesis (London 2012), which suggests that metric and rhythmic cognition are deeply enculturated. This study further demonstrates how variable timing merges seamlessly into variable rhythm in oral traditions. Timing measurements are then valuable alongside transcription and annotation for the representation and study of performance practice.